A convolution neural network for higher resolution dose prediction in prostate volumetric modulated arc therapy - Sumida, Iori; Magome, Taiki; Das, Indra J; Yamaguchi, Hajime; Kizaki, Hisao; Aboshi, Keiko; Yamaguchi, Hiroko; Seo, Yuji; Isohashi, Fumiaki; Ogawa, Kazuhiko (Physica medica, 2020)
•Convolution neural network (CNN) predicts high resolution dose distribution.•Proposed CNN predicts high resolution dose distribution faster.•Proposed CNN predicts accurate dose even in inhomogeneity region. This study aims to investigate the feasibility of using convolutional neural networks to predict an accurate and high resolution dose distribution from an approximated and low resolution input dose. Sixty-six patients were treated for prostate cancer with VMAT. We created the treatment plans using the Acuros XB algorithm with 2 mm grid size, followed by the dose calculated using the anisotropic analytical algorithm with 5 mm grid with the same plan parameters. U-net model was used to predict 2 mm grid dose from 5 mm grid dose. We investigated the two models differing for the training data used as input, one used just the low resolution dose (D model) and the other combined the low resolution dose with CT data (DC model). Dice similarity coefficient (DSC) was calculated to ascertain how well the shape of the dose-volume is matched. We conducted gamma analysis for the following: DVH from the two models and the reference DVH for all prostate structures. The DSC values in the DC model were significantly higher than those in the D model (p < 0.01). For the CTV, PTV, and bladder, the gamma passing rates in the DC model were significantly higher than those in the D model (p < 0.002–0.02). The mean doses in the CTV and PTV for the DC model were significantly better matched to those in the reference dose (p < 0.0001). The proposed U-net model with dose and CT image used as input predicted more accurate dose.